2021
DOI: 10.3389/fpsyt.2021.648751
|View full text |Cite
|
Sign up to set email alerts
|

A Correlative Study Between Personality Traits and the Preference of Site Selection in Cosmetic Treatment

Abstract: Background: Cosmetic treatment was closely associated with beauty seekers' psychological well-being. Patients who seek cosmetic surgery often show anxiety. Nevertheless, not much is known regarding how personality traits relate to the selection of body parts that receive cosmetic treatment.Aims: This study aims to investigate the correlation between personality traits and various selection sites for cosmetic treatment via Eysenck Personality Questionnaire (EPQ).Methods: A cross-sectional approach was adopted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…It has also been shown that extraversion in uences the choice of area in aesthetic surgical operations. In the aforementioned study, extraversion did not in uence the choice of rhinoplasty but was found to be effective in surgical choices for the facial contour area (9). Extraverted individuals typically have additional social needs, seek more social interaction, and pay attention to their appearance to gain energy from their surroundings (24).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It has also been shown that extraversion in uences the choice of area in aesthetic surgical operations. In the aforementioned study, extraversion did not in uence the choice of rhinoplasty but was found to be effective in surgical choices for the facial contour area (9). Extraverted individuals typically have additional social needs, seek more social interaction, and pay attention to their appearance to gain energy from their surroundings (24).…”
Section: Discussionmentioning
confidence: 90%
“…The same study found that neuroticism also in uenced the choice of surgery for skin and facial contour areas. In other words, neuroticism is particularly motivating for aesthetic surgeries, especially for the nose, eyes, and other body parts (9). Neuroticism can be associated with depression, anxiety, and emotional instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 People around the world value symmetry, harmony, and equilibrium as qualities of beauty and appeal; however, no two people from different ethnic or cultural backgrounds are likely to have the same aesthetic goals or perceptions of beauty. 3 As cosmetic surgery has become increasingly popular, and patients from diverse ethnic backgrounds seek interventions to maintain the balance and harmony of their natural features, beauty standards have become more diverse and vary according to cultural and ethnic norms [4][5][6][7][8] A survey of people from China, Taiwan, Japan, Hong Kong, and South Korea showed that each nation had its own expectations and preferences in terms of aesthetic results. 9 Traditional aesthetic criteria such as symmetry, averageness, youth, and sexual dimorphism may not be applicable to different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%